Differential diagnosis of opisthorchiid and heterophyid metacercariae (Trematoda) infecting flesh of cyprinid fish from Nam Ngum Dam Lake in Laos - Scholz, T; Ditrich, O; Giboda, M (The Southeast Asian journal of tropical medicine and public health, 1991)
The examination of flesh of 313 cyprinid fish from the Nam Ngum water reservoir in Vientiane Province, Laos, revealed the presence of four morphologically similar opisthorchiid and heterophyid metacercariae of medical importance. The following morphological characters, visible under dissecting microscope with low magnification, were typical of trematodes recorded in fish: (1) Opisthorchis viverrini, the liver fluke, has oval cysts containing quickly moving C-shaped metacercariae provided with a rather large excretory bladder; (2) metacercariae of Haplorchis pumilio and H. taichui are surrounded by a thin-walled, oval cyst; they are actively motile, C- or S-shaped, and possess a relatively small excretory bladder; (3) cysts of Haplorchoides mehrai are considerably variable in shape, size, and thickness of cyst wall; larvae are slowly moving, C- or S-shaped, or often not folded, and provided with a rather small excretory bladder. Some cysts with dead or degenerated H. mehrai larvae are filled with brownish or yellowish pigment. Morphological variability of some larvae, however, excluded correct identification of all metacercariae during routine examination of fish. Therefore, we consider isolation of several larvae from each fish host as well as all "atypical" metacercariae from fish flesh and their examination under the light microscope to be necessary. Even though this method of examination is rather time consuming, it decreases the possibility of false identification of trematode larvae encysted in flesh of cyprinid fish during field studies on opisthorchosis and heterophyiosis.
Keywords: Diagnosis, Differential; Animals; Fresh Water; diferenciální diagnóza; Heterophyidae; nemoci ryb; Laos; Opisthorchidae; zvířata; Fish Diseases; infekce červy třídy Trematoda; Fishes; sladká voda; Trematode Infections; ryby